Unveiling Political Persona Visual Framing Analysis of Presidential Candidates' Instagram Branding for the 2024 Indonesian Election - Putri, Ratu Mega Maulina; Ahmad, Nyarwi (Universitas Islam Negeri Raden Intan Lampung, 2023)
Personal branding on Instagram is becoming increasingly relevant in the context of political campaigns. The adoption of political branding concept provides candidates with the opportunity to build and manage their brand identity as a key element in their campaign strategy. This research will adopt a visual framing analysis approach using Kapferer's Brand Identity Prism as a theoretical foundation. Within this framework, this research will explore the dimensions of personal branding of the 2024 Presidential Election’s candidates in Indonesia, involving three main candidates, Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo. This research employs a qualitative approach with a descriptive analysis method, collecting data from the visual Instagram feeds of each presidential candidate (@aniesbaswedan, @prabowo, and @ganjar_pranowo), taken between October 26th and December 11th, 2023. It was found that each of the candidates reflects dimensions such as physique, personality, relationship, culture, reflection, and self-image in their Instagram posts. Through a deeper understanding of these personal branding strategies, this research can uncover their impact on voter perceptions and the dynamics of competition in the Indonesian political arena. Furthermore, by comprehending the characteristics of effective personal branding through visual framing analysis, candidates can optimize their political marketing strategies on Instagram.